Challenges for financial intermediaries offering asset decumulation products - Schich, Sebastian (OECD Publishing, 2009)
The present article focuses on issues related to asset decumulation. In discussing these issues, a key proposition is that financial institutions are most willing and able to offer decumulation products with fixed payment promises to the extent they are able to invest in financial assets that allow them to hedge a considerable part of the risks associated with the payment promises they extend.Indeed, what is sometimes overlooked in discussions bout shifts from asset accumulation to decumulation is that the decumulation phase also involves investment challenges, especially if specific patterns of payouts such as regular payouts of fixed amounts are aimed at. Many writers have argued for some time now that pension fund managers will have difficulty implementing asset-liability matching because there are insufficient quantities of suitable assets. As it turns out, the shortfall in hedging instruments extends to more than just the "toxic" tail of longevity risk, as is commonly being argued. The analysis in this article shows that hedging interest rate risk is also not as straightforward as one may think